PERANCANGAN AQUASCAPE CENTER DENGAN PENERAPAN ARSITEKTUR KONTEMPORER DI JAKARTA BARAT - Abdullah, Miftakhul Hikam; Sulistiowati, Anggraeni Dyah; Suryandari, Putri (MAESTRO, 2021)
Aquascape comes from the word Aquarium and Landscape which means the art of managing plants, water, rocks, corals, and wood in an aquarium whose beauty can be seen and felt by all the general public and aquascape lovers themselves. Aquascape art is an art that is quite complicated because it requires patience and creativity in conceptualizing and creating the aquascape itself. The contemporary architectural concept is a building concept that emphasizes freedom of expression, shows a unique shape and contrasts with the surrounding environment. The contemporary architectural concept is characterized by an unusual building shape. Contemporary architecture tends to use curved lines more often as the main style. That is what is the main attraction of this building